Perception and experience of online classes among undergraduate and postgraduate medical students during COVID-19 - Suman Sharma; Brihaspati Sigdel (Journal of Gandaki Medical College, 2022)
Introduction: The purpose of this study was to analyze the perception and experiences of online classes among undergraduate and post-graduate medical students during COVID-19.